Estratégia competitiva e difusão de tecnologia no setor produtivo cafeeiro do Sul de Minas Gerais - Drummond, Ricardo Luiz Araújo (2003)
This work presents a description ofthe coffee productive sector in the south region ofMinas Gerais state, Brazil. The aproach ofthe study was focused on the competitive strategy, specifically, the use ofinformation technology (IT), trading practices, and financing types; and transfer and difusion oftechnology, analysing the use and perceptions ofthe agents towards the different sources of information, and aproaching questions about the realization ofcourses. Atotal of 243 coffee producers and 52 professionals connected to coffee producing activities were interviewed. The main conclusions of the present study were (a) the coffee producers are aware of the need to be actualyzed and open to innovations; (b) the heterogenity ofcoffee farms and productivity systems may be a limitation to the formulation of development strategies to the coffee productive sector, (c) the use ofIT inside the properties is already a reality; (d) the use ofIT in the integration ofthe different sectors ofthe coffee agribusiness is still limited; (e) there is no standardization among the softwares used by the producers; (0 the main source ofinformation used by the coffe growers is the cooperatives; (g) itisstill early to measure the impact ofthe use ofcomputers in the coffee's productive chain; (h) the fact that the producers do not have a trading plan may be a limitant factor in the competitiveness ofthe productive sector; (i) the productive sector still depends on the government financing; (j) the events made to transfer technology are limited to the higher classes producers.